Analyzing novices' fun and programming behaviours while playing a serious blocks-based game - Vahldick, Adilson; Marcelino, Maria José; Mendes, António José (Revista Brasileira de Informática na Educação, 2021)
Blocks-based environments have been used to promote programming learning mostly in elementary and middle schools. In many countries, isolated initiatives have been launched to promote programming learning among children, but until now there is no evidence of widespread use of this type of environment in Brazil and Portugal. Consequently, it is common that many students reach higher education with little or no programming knowledge and skills. NoBug’s SnackBar is a game designed to help promote programming learning. This study examined students' behavior and attitudes when playing the game on their initiative. It used a sample of 33 undergraduate students enrolled in an introductory programming course. The variables studied were students' performance and engagement, satisfaction, and problem-solving strategies. The main findings were (1) better performing students had a high level of perceived learning, (2) all the students had similar perceptions about their fun while playing, (3) the leader board was the most used game element not directly related to learning and (4) the top-ranked students access previous solutions to help them solve a new mission, while the others often use a trial-and-error approach.